Wij nach einem Roman von Nikolai Gogol - Gogol', Nikolaj Vasil'evic (RUSCICO, 2000)
"Viy" tells the story of a mischievous theology student named Thomas Brutus who is called to read scripture beside the coffin of a recently deceased young woman. For three consecutive evenings, her father locks Thomas inside the rural church/barn where his daughter's coffin has been placed. Promptly at midnight, she then rises from the coffin - for she was a witch - and a savage battle takes place between the forces of good and evil. With chalk, Thomas marks off a circle around himself, and this keeps the evil forces from destroying him. But this doesn't stop the witch from trying her best to overpower him. Ultimately she calls forth the denizens of hell to assist her. "Viy" comes from a folk tale tradition that is largely foreign to American audiences. The closest American counterpart might be Washington Irving's "The Legend of Sleepy Hollow," which contains some of the same mix of horror and folk humor as "Viy". [www.imagesjournal.com]